Application of Stemmer Algorithm to Determine Dhomir Mustatir in a Kalimah Fi’il - Sri Lestanti; Fauzi Asrofi (JOSAR (Journal of Students Academic Research), 2021)
The nahwu subject is one of the subjects that form the basis of the world of Islamic boarding schools. Nahwu becomes the foundation for students in studying the yellow book. In the science of nahwu, there are several basic chapters that must be understood by students, one of which is the Dhomir Dhomir chapter, which is one of the chapters in the science of nahwu that must be studied for students in Islamic boarding schools. In the dhomir chapter, students will learn about a pronoun consisting of 14 dhomirs. Dhomir learning is usually done using the word-by-word memorization method, in this memorization, there are still many students who have difficulty finding changes in the form of one word into another so that it will hinder the learning process of the students. Based on this problem, the writer takes the title of applying a stemmer algorithm to determine dhomir mustatir in a sentence of fi'il. This study produces an application that can determine a pronoun or dhomir in a fi'il sentence with 14 applicable dhomir rules. From the test results obtained a percentage of 97% of the level of system compatibility with the form of word changes or dhomir.